The pottery (Scottish Historical and Archaeological Internet Reports, 2005)
The pottery assemblage from Olcote cairn comprises 42 sherds from a near-complete cremation urn with a total weight of 1094 g, plus a further 397 sherds and fragments weighing 2248 g. The minimum number of vessels represented is 20. The majority of the pottery consists of plain body sherds and, apart from the urn, there are only 17 diagnostic sherds: five plain rim sherds, three decorated rim sherds and nine decorated body sherds. The sherds are mostly very small, with an average weight of only 6 g (excluding the urn); many of them are also abraded. Pottery was recovered from contexts throughout the cairn and from pre-cairn and post-cairn horizons.